Stingless Bee (Trigona sp.) Beekeeping as an Alternative Economic Source to Support Community Food Security in Lempake, Samarinda - Akhmat Rizkuna; Suhardi Suhardi; Ari Wibowo; Anhar Faisal Fanani; Nurul Fajrih H; Nurliani Erni; Dinar Anindyasari; Karenina Dwi Yulianti; Fandini Melia Anjani (Lembaga Pengembangan Kinerja Dosen, 2025)
Stingless bee (Trigona sp.) cultivation presents significant potential for livestock diversification, improved food security, and rural economic development. Although this practice offers clear advantages, including low maintenance requirements, minimal environmental risk, and the high nutritional and commercial value of its honey, its adoption in Lempake Subdistrict, North Samarinda, East Kalimantan, remains limited. This situation is primarily due to a lack of community awareness and technical knowledge in apiculture. In response, a community service program was conducted on 10 May 2025 by lecturers from the Faculty of Agriculture, Mulawarman University, in collaboration with local farmer groups and supported by the Samarinda City Government. The program provided structured training through field visits, lectures, interactive discussions, and practical demonstrations at selected apiaries. Post-training evaluations showed a substantial improvement in participants’ understanding of colony management, hygienic honey harvesting, and the economic prospects of stingless bee products. Additionally, the program encouraged entrepreneurial interest and supported the development of value-added functional food products based on local resources. These findings indicate that targeted training and institutional collaboration are effective in promoting sustainable stingless beekeeping practices. Future initiatives should focus on continued technical support and the integration of apiculture products into local and digital markets to enhance competitiveness and economic impact.